Is 5‐fluorouracil the best candidate for topical chemoprevention of skin cancers in organ transplant recipients?. (28th April 2022) - Samimi, Mahtab
Abstract : Linked Article: Hasan et al. Br J Dermatol 2022; 187:324–337.